Development and validation of a sensitive method for simultaneous determination of rosuvastatin and N‐desmethyl rosuvastatin in human plasma using liquid chromatography/negative electrospray ionization/tandem mass spectrometry. (30th May 2013) - Lee, H. K.; Ho, C. S.; Hu, M.; Tomlinson, B.; Wong, C. K.
ABSTRACT A sensitive and specific liquid chromatography tandem mass spectrometric method was developed and validated for the simultaneous determination of rosuvastatin (ROS) and N‐desmethyl rosuvastatin (NOR‐ROS) in human plasma using deuterium‐labeled internal standards. The plasma samples were prepared using liquid–liquid extraction with diethyl ether. Chromatographic separation was accomplished on an Xterra MS C18 column. The mobile phase consisted of a gradient mixture of 15 µmol/L ammonium acetate in water and in methanol, maintained at a flow rate of 0.4 mL/min. Mass spectrometric detection was carried out in negative electrospray ionization mode and monitored by quantification and qualification transitions for each analyte. Using 300 μL plasma samples, the lower limits of quantification of ROS and NOR‐ROS were 0.05 and 0.02 µg/L respectively. The linearity of ROS and NOR‐ROS ranged from 0.05 to 42 and 0.02 to 14 µg/L respectively. The relative standard deviations of ROS and NOR‐ROS were <13 and 9%, respectively, while the deviations from expected values were within −4.7–9.8 and −5.2–4.6%, respectively. The present method offered high sensitivity and was successfully applied to a 24 h pharmacokinetic study of ROS and NOR‐ROS in healthy subjects receiving a single dose of 10 mg ROS. Copyright © 2013 John Wiley & Sons, Ltd.